2015
DOI: 10.1080/15384047.2015.1040960
|View full text |Cite
|
Sign up to set email alerts
|

Tumor infiltrating lymphocytes in ovarian cancer

Abstract: The accumulation of tumor infiltrating lymphocytes (TILs) in ovarian cancer is prognostic for increased survival while increases in immunosuppressive regulatory T-cells (Tregs) are associated with poor outcomes. Approaches that bolster tumor-reactive TILs may limit tumor progression. However, identifying tumor-reactive TILs in ovarian cancer has been challenging, though adoptive TIL therapy in patients has been encouraging. Other forms of TIL immunomodulation remain under investigation including Treg depletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
229
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(257 citation statements)
references
References 142 publications
6
229
2
2
Order By: Relevance
“…Indeed, the prognostic value of intraepithelial Treg infiltration in ovarian cancer is still in debate [5, 30]. Some studies showed that Treg infiltration was associated with decreased overall survival in ovarian cancer [17, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the prognostic value of intraepithelial Treg infiltration in ovarian cancer is still in debate [5, 30]. Some studies showed that Treg infiltration was associated with decreased overall survival in ovarian cancer [17, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies assessed the prognostic value of tumor-infiltrating lymphocytes in various types of tumors, such as breast cancer, gastric cancer, non-small cell lung cancer, and ovarian cancer 3841 . Many results indicated that TILs may be clinically significant prognostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The diverse array of immune evasion mechanisms employed by tumors highlights the necessity for combination and synergistic therapies. Here, we discuss major drivers of T cell dysfunction in the context of three solid tumors: 1) melanoma, in which T cell responses exist and frequently can be enhanced to mediate anti-tumor activity (Rosenberg and Restifo, 2015), 2) ovarian cancer, in which potentially beneficial T cell responses exist in a subset of patients, but have proven difficult to augment (Santoiemma and Powell, 2015) and 3) PDA, in which endogenous T cell responses are rare (Emmrich et al, 1998; Ene-Obong et al, 2013; von Bernstorff et al, 2001). …”
Section: Introductionmentioning
confidence: 99%